Effect of jute retting on the physico-chemical andbiological condition of water - Dasgupta, M; Goswamy, S; Goswamy, A (Indian Journal of Fisheries, 2011)
An investigation was carried out to find out the effect of jute retting on thephysico-chemical and biological condition of water of an experimental waterbody. There was no significant variation in the physico-chemical parametersexcept for the increase of COD and BOD for a short period when fish mortalitywas observed. There was no qualitative variation in the plankton population.However, plankton population decreased during the jute retting period andincreased in the post jute retting period. Hence jute retting has both detrimentaland favourable effect on the aquatic ecosystem. For a short period it creates ananaerobic condition and there may be fish mortality if the retting is done in asmall closed water body. But with the passage of time the nutrients releasedfrom the decaying jute,Â help the growth of the aquatic life.